(untitled) (LIS TODAY, 2021)
We are living in technology era, everyone is using technological devices. Smartphone is also one of them. Smartphones are providing various applications like internet, e-mail, weather update, academic related various apps, short message device, video call facilities, current news, access document from anytime and anywhere and retrieval of information. The smartphone device is working as a multi functional device. The Smartphone is an information gadget for retrieving information for students. It can also easily portable device. In the other words today, smartphone works like a computer. We can say that smartphone is a combination of computer. This article related to my Master degree dissertation work.